Enhancing Consumer Protection in the Indonesian Financial Service Sector through the Utilization of Standardized Contracts - Abubakar, Lastuti; Handayani, Tri (Yustisia, 2023)
The Financial Services Sector is a pioneer in developing standard contract regulations. This standard contract complements Contract Law that did not initially regulate standard contracts. This study aims to analyze the development of standard contract regulation in the Indonesian financial services sector. It examines aspects that require strengthening so that standard contracts can become a protecting consumer tool in the financial services sector. This study uses a normative juridical approach with a descriptive-analytical research specification. The results show that: 1) The development of standard contract regulations in the POJK on Consumer Protection used by Financial Service Business Actors (PUJK) contains the principles and prohibitions on including exoneration clauses and undue influence. This provision fills the legal vacuum regarding standard contracts that still refer to the freedom of contract principle and Book III of the Civil Code and other related regulations. The use of the standard contracts encourages PUJK to comprehend the importance of consumer protection; 2) OJK should strengthen regulatory aspects by issuing guidelines on standard contract formats and contain correct interpretations of the scope of undue influence and supervise the standards contract both directly and indirectly that have been implemented by PUJK.